A Cross-Section Analysis of Demand Deposit Variability - Murphy, Neil B. (Journal of Financial and Quantitative Analysis, 1968)
Commercial bank portfolio models developed by Hester [6], Porter [11], and Kane and Malkiel [7], among others, relate the structure of an asset portfolio to variation in the level of deposits. Similarly, in a recent application of linear programming to asset management, Cohen and Hammer [3] specify a liquidity constraint based upon deposit fluctuations. However, there have been few empirical studies of the determinants of demand deposit fluctuations. The purpose of this paper is to extend the work of Gramley [4], Rangarajan [12], and Wilkerson [14] on the determinants of deposit variability. In this paper, the analysis will be confined to demand deposit variability.